Guía de prácticas de laboratorio STEM de física con materiales del entorno para el aprendizaje de los conocimientos de dinámica de los estudiantes de primero de bachillerato ciencias de la Unidad Educativa Comunitaria Intercultural Bilingüe San Juan de Ilumán en el Año Lectivo 2023-2024 - Sánchez Rodríguez, Luis Germán (2024)
In general, physics is considered experimental in education, for this reason this research aims to determine the importance of using environmental and low-cost material as support in the teaching-learning of the subject of physics, aimed at strengthening knowledge. of the students of the first year of the unified general high school of the Intercultural Bilingual Community Educational Unit “San Juan de Iluman” in order to understand natural phenomena, it must be studied theoretically together with experimental practice, here the role played by the teacher is guide and provide the necessary tools so that the student develops all his or her abilities and is the creator of his or her own knowledge. The change in focus, pedagogical methodologies and inclusion of teaching material guide for laboratory experiments have produced positive changes in learning and academic results in students between academic periods, which consolidate the hypothesis that a change of model should be made. current pedagogical approach to a participatory and experiential one in which it is possible, through activities focused on reality, to allow the student to actively participate, having meaningful and beneficial learning. Students and teachers want a guide to laboratory practices, with elements that can be found and reused in the environment, supported with multimedia that allows them to understand the procedures and concepts of what is developed in the laboratory experiments, being an inclusive, easy material. understandable for the vast majority and with proposals for practices that the text currently used does not always have it, in addition to being difficult to understand.